The neutrophil elastase inhibitor, sivelestat, attenuates acute lung injury in patients with cardiopulmonary bypass - Pan, Tuo; Tuoerxun, Tayierjiang; Chen, Xi; Yang, Cheng-Jin; Jiang, Chen-Yu; Zhu, Yi-Fan; Li, Ze-Shi; Jiang, Xin-Yi; Zhang, Hai-Tao; Zhang, He; Wang, Ya-Peng; Chen, Wei; et al. (Frontiers in Immunology, 2023)
Background: The sivelestat is a neutrophil elastase inhibitor thought to have an effect against acute lung injury (ALI) in patients after scheduled cardiac surgery. However, the beneficial effect of sivelestat in patients undergoing emergent cardiovascular surgery remains unclear. We aim to evaluate the effect of sivelestat on pulmonary protection in patients with ALI after emergent cardiovascular surgery. Methods: We firstly performed a case-control study in 665 patients undergoing emergent cardiac surgery from January 1st, 2020 to October 26th, 2022, including 52 patients who received sivelestat (0.2mg/kg/h for 3 days) and 613 age- and sex-matched controls. Secondly, a propensity-score matched cohort (sivelestat vs control: 50 vs 50) was performed in these 665 patients. The primary outcome was a composite of adverse outcomes, including 30-days mortality, ECMO, continuous renal replacement therapy (CRRT) and IABP, etc. The secondary outcome included pneumonia, ventricular arrhythmias and mechanical ventilation time, etc. Results: In propensity-matched patients, the 30-day mortality (16% vs 24%, P=0.32), stroke (2% vs 8%, P=0.17), ECMO(6% vs 10%, P=0.46), IABP(4% vs 8%, P=0.40) and CRRT(8% vs 20%, P=0.08) had no differences between sivelestat and control group; sivelestat could significantly decrease the pneumonia (40% vs 62%, P=0.03), mechanical ventilation time (median: 96hours, IQR:72-120hours vs median:148hours, IQR:110-186hours, P<0.01), bilateral pulmonary infiltrates (P<0.01), oxygen index (P<0.01), interleukin-6(P=0.02), procalcitonin(P<0.01) and C-reactive protein(P<0.01). Conclusion: Administration of sivelestat might improve postoperative outcomes in patients with ALI after emergent cardiovascular surgery. Our results show that sivelestat may be considered to protect pulmonary function against the inflammatory injury by CPB.